Healthy Living Counseling Through Washing Hands Against Germs At State Elementary School Cisalak 3 In 2025 (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Handwashing with soap is one of the most effective and accessible methods to prevent the transmission of infectious diseases in school-aged children. However, observations at Cisalak 3 Public Elementary School indicate that most students have not yet implemented proper handwashing behavior, necessitating the implementation of the (Handwashing Against Germs) community service program. This activity aims to improve students' knowledge, attitudes, and handwashing practices through an educational seminar method with a pretest–posttest approach implemented through the delivery of health materials, interactive discussions, demonstrations of handwashing techniques according to World Health Organization (WHO) standards, and hands-on practice with guidance. A total of 169 students from grades 1 to 6 of Cisalak 3 Public Elementary School participated as participants. The results of the activity showed a significant increase in all measured indicators. Students' knowledge increased from 28% in the pre-test to 55% in the post-test. Students' attitudes toward important handwashing times increased from 38% to 72%, and correct handwashing behavior increased from 41% to 86% after the intervention. The findings of this activity indicate that health seminars accompanied by demonstrations and hands-on practice are effective in improving elementary school students' knowledge, attitudes, and handwashing behavior. Recommendations from this activity include the integration of handwashing education into daily school routines, the provision of adequate handwashing facilities, and the ongoing implementation of health education to strengthen the implementation of Clean and Healthy Living Behaviors (PHBS) in the school environment.